The Role of Gender for Cross-Sectoral, Transformative Change - Bryan, Elizabeth (2019)
Elizabeth Bryan POLICY SEMINAR Bigger Change Faster: Integrated Development, Health, and Environment Actions for a Sustainable Future Co-Organized by IFPRI, The Nature Conservancy, PATH, and Duke University OCT 23, 2019 - 12:15 PM TO 01:45 PM EDT